ANALISA PENGARUH KUALITAS WEBSITE SHOPEE PADA KEPUASAN PENGGUNA MENGGUNAKAN METODE WEBQUAL 4.0: ANALYSIS OF THE INFLUENCE OF SHOPEE WEBSITE QUALITY ON USER SATISFACTION USING THE WEBQUAL 4.0 METHOD - Isaac Julio Herodion (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The quality of e-commerce websites has a significant impact on user satisfaction, which in turn influences purchasing behavior and customer loyalty. This study aims to analyze the effect of Shopee’s website quality on user satisfaction using the WebQual 4.0 framework, which includes three dimensions: usability, information quality, and interaction quality. A quantitative approach was employed, involving an online survey distributed to 100 active Shopee users. The collected data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that all three WebQual 4.0 dimensions have a positive and significant influence on user satisfaction, with usability being the most dominant factor. These findings highlight the importance of intuitive interface design and efficient navigation in enhancing user experience. The study offers practical implications for website developers and e-commerce managers in formulating strategies to improve platform quality in order to maximize user satisfaction and loyalty.